Breathing catalyst-supports: CO2 adjustable and magnetic recyclable "smart" hybrid nanoparticles. Issue 99 (11th October 2016) - Feng, Anchao; Wang, Yun; Peng, Liao; Wang, Xiaosong; Yuan, Jinying
Abstract : A CO2 stimulated, magnetic recyclable catalyst with stable catalytic performance is designed and illustrated by the combination of recently developed chemistry on CO2 responsive polymers and nanoparticle technique. Abstract : A facile route for fabricating CO2 gas stimulated, magnetically recyclable hybrid nanoparticle is designed and illustrated through introducing a CO2 sensitive polymeric matrix and gold nanoparticles (AuNPs) onto the surface of magnetic Fe3 O4 @SiO2 nanospheres. The accessibility of the AuNPs to the reaction substrates can be tuned following swollen or collapsed of CO2 sensitive shell, which may leads to an increase or decrease of catalytic activity. Therefore, the obtained hybrid system offers a novel strategy to adjust and control the catalytic activity through mild stimulation of CO2 /N2, where the magnetic core assures a magnetically recyclable catalysis.